2014
DOI: 10.1002/eco.1584
|View full text |Cite
|
Sign up to set email alerts
|

Generation of storm runoff and the role of animals in a small upland headwater stream

Abstract: This paper illustrates the hillslope storm runoff mechanisms and the effects of livestock in upland areas. The research site was a small upland catchment area on Dartmoor (Southwest England). It was shown that overland flow on the tracks and paths created by animals in the area responded very rapidly to rainfall, in the same order of magnitude as stream runoff. Livestock stocking densities were significantly different in different vegetation compositions. The topsoil bulk density values, moisture content and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Land‐use alone does not significantly improve prediction because its importance is already captured within the interaction terms. Modelling results compare well with Meijles et al (2006) and Meijles et al (2015), who concluded that vegetation was the dominant control on soil wetness during “dry” conditions at Dartmoor (semi‐natural grassland).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Land‐use alone does not significantly improve prediction because its importance is already captured within the interaction terms. Modelling results compare well with Meijles et al (2006) and Meijles et al (2015), who concluded that vegetation was the dominant control on soil wetness during “dry” conditions at Dartmoor (semi‐natural grassland).…”
Section: Resultssupporting
confidence: 84%
“…This may be because of weak vegetation differentiation within the SNG plot, with many sampling grids containing both rush and grass species. Other studies have more successfully differentiated semi‐natural grassland vegetation species, with Meijles et al (2015) outlining that moorland grasses saturate faster than heather or bracken ( Pteridium aquilinum ). Conversely to the SNG plot, soil beneath common rushes in PP was wetter than ryegrass during August and October sampling dates, although similar in May and November (Table 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This connectivity results in the rapid conversion of water to stream T A B L E 3 The influence of newly established woodland on surface soil physical properties along the four study river catchments located in Dartmoor, SW England Note: M (±SE and SD) values of surface soil compaction (Kpa), bulk density with stones (g cm −3 ) (BD), macro-porosity (%) (M porosity), percentage of small stones (%) and organic matter (%) (SOM) of soils in establishing 'woodland' sites are compared with control grazed 'pasture' areas using two-way ANOVA with significant (p ≤ .05) differences denoted in bold font. The tion (Meijles, Dowd, Williams, & Heppell, 2015;Meyles et al, 2006). It is likely, therefore, that establishing woodland offers effective NFM by reducing the number of wet source areas, the connectivity of hillslope moisture and the conversion of rainfall to stream discharge.…”
Section: Discussionmentioning
confidence: 99%